Tunable Q-switched Erbium-Doped Fiber Laser Using Gold Nanoparticles Saturable Absorber - Rizman, Zairi Ismael; Rusdi, Muhammad Farid Mohd; Arof, Hamzah; Latiff, Anas Abdul; Apsari, Retna; Harun, Sulaiman Wadi (Old City Publishing, 2019)
We have fabricated gold nanoparticles (GNP) based saturable absorber and used it to passively Q-switch an Erbium-doped fiber laser (EDFL). By adjusting a tunable filter, the laser operation is tunable from 1535 to 1560 nm. The highest slope efficiency of 23.38% is obtained at 1545 nm. At this operation wavelength, the repetition rate of the self-starting Q-switching pulses is increased from 19.2 to 36.4 kHz, while the pulse width is reduced from 18.2 to 11.1 μs, with increasing pump power from 14.9 to 37.7 mW. The maximum pulse energy of 195 nJ is obtained at 37.7 mW pump power. The proposed Q-switched laser is simple, cost-effective and thus suitable for environmental sensing, metrology and biomedical diagnostics ©2019 Old City Publishing, Inc.